2021
DOI: 10.1088/1361-6668/ac1aad
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘High- Tc superconductivity in H3S: pressure effects on the superconducting critical temperature and Cooper pair distribution function’

Abstract: The Monkhorst–Pack scheme is applied in a recent article in (2019 Supercond. Sci. Technol. 32 125013) implying exclusion of the umklapp phonons. But in a superconductor scattered electrons can land anywhere on the Fermi surface so that umklapp phonons must be included. The authors should take care to explain if and how the original Monkhorst–Pack scheme was modified to accommodate umklapp phonons for electron-phonon scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 2019, Camargo-Martı ´nez, Gonza ´lez-Pedreros and Baquero studied the pressure effect on high-T c superconductivity in H 3 S. 24 In response to our enquiry in ref. 50, they confirmed that ''the electron-phonon umklapp process has a vital relevance in explaining the behaviour of electrical resistance'' but claimed ''in the total absence of electrical resistance, . .…”
Section: Umklapp Phonons: Recent Advancesmentioning
confidence: 83%
See 2 more Smart Citations
“…In 2019, Camargo-Martı ´nez, Gonza ´lez-Pedreros and Baquero studied the pressure effect on high-T c superconductivity in H 3 S. 24 In response to our enquiry in ref. 50, they confirmed that ''the electron-phonon umklapp process has a vital relevance in explaining the behaviour of electrical resistance'' but claimed ''in the total absence of electrical resistance, . .…”
Section: Umklapp Phonons: Recent Advancesmentioning
confidence: 83%
“…In 2019, Camargo-Martínez, González-Pedreros and Baquero studied the pressure effect on high- T c superconductivity in H 3 S. 24 In response to our enquiry in ref. 50, they confirmed that “the electron–phonon umklapp process has a vital relevance in explaining the behaviour of electrical resistance” but claimed “in the total absence of electrical resistance, …, perhaps an electron that undergoes the umklapp-process will contribute to electrical resistance rather than the superconducting phase”. 25 In short, they believe the umklapp process does not contribute much to superconductivity.…”
Section: Umklapp Phonons: Recent Advancesmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the Umklapp phonons come from anharmonic terms. Some authors 23 25 suggest that Umklapp phonons must be included in theoretical studies that evaluating phonon interaction effects at high-temperature conditions (like room-temperature for superconductors). However, the presence of umklapp process is mainly associated with the electrical resistivity 26 29 , which is measured in the normal state and not in the superconductor one.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Possibly, we need to include three-and four-phonons anharmonic terms or perhaps propose a modified Eliashberg function. Also,'the umklapp phonons are not replicas of normal phonons' [8]. This is not trivial topic.…”
mentioning
confidence: 99%